Fauna associated to bromeliad Vriesea procera (Martius ex Schults Filius) Wittmack in rubber trees monocultures in Michelin Ecological Reserve (Southern Bahia, Brazil) - Rondinelli, Simone Franco; Cambuí, Elaine Cristina Barbosa; Nogueira, Marcos Moura; Vargens, Marta Muniz Freire; Camardelli, Milena Cordeiro (SITIENTIBUS série Ciências Biológicas, 2008)
Bromeliads with rosette form attract diverse animal species because they offer shelter source, humidity, development and reproduction. The objective was to verify if there was difference in the faunal composition associated to the Vriesea procera between two areas of culture of the rubber-tree, in Michelin Ecological Reserve. 20 bromeliads have been collected in managed and not managed rubber plantations and the faunal species have been identified in level of morphological species. The ANOSIM detected significant difference and the NMDS showed the sample units forming two distinct groups. When the two treatments were compared, the areas managed presented greater abundance of the most representative groups, probably for the lesser variety of microhabitats found in these places. Vriesea procera, being the only species of Bromeliaceae found in the managed areas, has still a more significant role on the structure of the local community, especially for those individuals that possess life cycles dependent on the phytotelms.